Analysis of Health Level Performance of Amil Zakat Institution Entities with the Indonesian Zakat & Development Report (IZDR) Approach - Miftachur Rochmah; Imelda Dian Rahmawati (Universitas Muhammadiyah Sidoarjo, 2023)
The research used qualitative research method with an evaluation approach. The data collection was carried out in two ways, that are by direct interviews with informants, which included the chairman, secretary, treasurer of LAZISNU and chairman, secretary, treasurer of Yayasan Kotak Amal. Second, by collecting data in the form of reports on changes in funds for 2020 and 2021, vision and mission, organizational structure, Standard Operating Procedures (SOP), and strategic plan documents. The data processing technique in this study is a reduction technique, which is reconfirming whether the data obtained is very relevant or selecting the required data. The results of this research showed that the performance levels of the two institutions, LAZISNU Sidoarjo and Yayasan Kotak Amal Sidoarjo were as follows: LAZISNU's performance level was the highest score achieved in financial performance then management performance. Meanwhile, the lowest performance was found in the performance of social legitimacy programs.Overall, the score obtained is 6.8 or A+, while the level of performance of the Yayasan Kotak Amal is known that the highest score is achieved in management performance then financial performance. Meanwhile, the lowest performance is in the performance of social legitimacy. Overall, the score obtained is 6.5 or A-.Based on the research above, the researcher gives advice to LAZISNU and Yayasan Kotak Amal to always improve performances which has a major influence on the Amil Zakat Institutions.